Pelvic floor symptoms in female cyclists and possible remedies: a narrative review. Issue 4 (April 2016) - Trofaier, Marie-Louise; Schneidinger, Cora; Marschalek, Julian; Hanzal, Engelbert; Umek, Wolfgang
Abstract Introduction and hypothesis Cycling has become a popular athletic activity worldwide and can lead to genital and pelvic floor dysfunction. This review summarizes the current body of evidence about the epidemiology of genital and pelvic floor symptoms in female cyclists, the therapy, and preventive interventions. Methods Two electronic meta-databases, OvidSP™ and Deutsches Institut für Medizinische Dokumentation und Information (DIMDI), comprising 40 individual databases, were searched for studies that described genital and pelvic floor symptoms in association with cycling and studies that tested possible therapies and prophylactic measures. For the literature search we explored the search terms "female", "bicycling", "pelvic floor", "lower urinary tract symptoms", and "vulvar diseases". Results The search retrieved 1, 219 articles, leaving 763 articles after removal of duplicates, and finally 12 articles eligible for review. We assessed 10 observational and 2 experimental studies. Genital and pelvic floor symptoms related to bicycling were pain, tenderness, neuropathy, urological dysfunction and skin lesions. Broader and conventionally shaped saddles were associated with fewer symptoms compared with cut-out saddle designs. Conclusion The quality of existing studies is generally low, but there is evidence that female cyclists suffer from similar problems to male cyclists, ranging from minor skin lesions to severe sequelae such as pain and neurological deficiencies.